Indonesian TV anchors’ final -k sound shift: The nature and the cause - Irnanda, Septhia; Yoestara, Marisa; Ismawirna, Ismawirna; Faisal, Faisal (Universitas Pendidikan Indonesia, 2022)
This study aimed, firstly, to observe the phonological change of the Standard Indonesian (SI), particularly the final-k syllabic pronunciation used in the journalistic videos aired between 1980 – 2019. Secondly, the study investigated the nature of the sound change by taking into account the theories of Lexical Diffusion. Lastly, the plausibly cause of the sound change was figured out, considering the sociolinguistic factors; orthographic re-regulation, post-colonial language policy, borrowing, and contacts. Methodologically, it is a diachronic study using a set of television news videos as the main source of data. A battery of findings from other related studies was employed to support the discussion on the nature and the reason for the sound change. The results show that the phonological shift of coda /ʔ/ /k/ happened to most final -k syllabic words across the periods observed, but with varying degrees of rapidity, where the high-frequency words tend to be more sustained. The results also indicated that phonological shift of coda /ʔ/ /k/ that occurred in the Indonesian TV-broadcast language was transferred from the Jakartan dialect, although some evidence of the 1972’s alphabetic writing system reformation also plays a considerable role in the TV News readers’ final -k sound shift.